Glacier Lake Outburst Floods in Nepal - Mool, P. K. (Journal of Nepal Geological Society, 1995)
The most active glaciers of Nepal, and adjoining Tibet in China, are located in the eastern part of the region. There are numerous occurrences of glacier lakes in this region. There are evidences that Glacier Lake Outburst Floods (GLOFs) have occurred throughout the Himalaya. However there is no detailed catalogue of the number and location of these past events. Most of the known cases occurred on the major rivers in the Kosi basin. The transport of sediment during GLOFs can be exceptionally high, with suspended sediment concentrations as high as 350,000 mg/l. The vertical and lateral erosion of the stream channel has the potential to destabilise talus slopes, former debris flows and landslides and to initiate new ones. The impacts of GLOFs downstream are extensive loss of human lives and cattle, loss of infrastructures, destruction of land, and interruption of tourism in mountainous areas. The GLOF on 11 July 1981 from Zhangzanbo Lake destroyed the diversion weir at the Sun Kosi Hydro Project in Nepal. The GLOF on 4 August 1985 from Dig Tsho lake along the Bhote (Dudh) Kosi destroyed the nearly completed Namche Small Hyde) Project. Even the very small GLOF of Chubung on 12 July 199 1, destroyed six houses and a long stretch of river banks in Beding village, in the Rolwaling Valley. Compilation of the inventory of glaciers and glacier lakes using remote sensing technology is the first step in identifying the occurrence of GLOF prone areas. Mitigating the impact of a GLOF surge can be done by reducing the volume of water in the glacier lakes in order to reduce the peak surge discharge. This can be achieved by: controlled breaching; construction of an outlet control structure; pumping out of a lake; and construction of a tunnel through the moraine barrier, or under an ice dam. Preventive measures, such as blasting masses of loose rock and ice, can be applied to ensure against avalanches into lakes.